1988
DOI: 10.1073/pnas.85.13.4842
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of antibody-alkaline phosphatase conjugates in combination with etoposide phosphate.

Abstract: Two anti-tumor monoclonal antibodies, LX (anticarcinoma) and 1F5 (anti-B lymphoma), were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(115 citation statements)
references
References 13 publications
7
106
0
2
Order By: Relevance
“…AP in the bile was found to be responsible for this phenomenon. The latter conclusion of the present study is based on indirect evidence, but others have shown that etoposide is rapidly converted to etoposide by AP in vitro (Senter et al, 1988).…”
Section: Discussionmentioning
confidence: 45%
“…AP in the bile was found to be responsible for this phenomenon. The latter conclusion of the present study is based on indirect evidence, but others have shown that etoposide is rapidly converted to etoposide by AP in vitro (Senter et al, 1988).…”
Section: Discussionmentioning
confidence: 45%
“…Enzymic activation of a less cytotoxic prodrug in the vicinity of the target cells has been demonstrated to lead to increased therapeutic efficacy. An example is the enhanced effect of antibody-alkaline phosphatase conjugate of etoposide phosphate both in vitro and in vivo (97).…”
Section: Immunotoxinsmentioning
confidence: 99%
“…Monoclonal antibodies can also be used for tumour-selective delivery of an enzyme that converts a relatively non-toxic prodrug into its toxic drug. This approach is called antibody-directed enzyme prodrug therapy (ADEPT) (Bagshawe, 1987;Senter et al, 1988). The idea of using antibodies to localize enzymes to the tumour was originally conceived by Philpott et al (1973).…”
mentioning
confidence: 99%